Effect of triamcinolone acetonide injection on pterygium recurrence in postoperative subconjunctival patients - Bellarinatasari, Nika (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2023)
Pterygium is an eye disorder characterized by fibrovascular tissue from the bulbar conjunctiva encroaching on the cornea. Inflammation has been suggested to play a role in the pathogenesis of pterygium, indicated by elevated levels of anti-inflammatory cells and markers. Triamcinolone acetonide is a steroid commonly used to treat eye diseases. This study evaluated the effects of anti-inflammatory triamcinolone acetonide injection after the pterygium surgery. This study included 71 eyes of 71 patients. The patients were divided into two groups: triamcinolone and control group. Each eye received a subconjunctival triamcinolone injection of 2.5 mg/ 0.1 ml or no after pterygium surgery with bare sclera technique. The infusion was done around the excision area. Before and after the surgery, the ocular pressure was evaluated. Topical steroid antibiotics and oral analgesics were administrated. The outcomes were assessed one day, week, three weeks, and one month after surgery under slit-lamp examination and noncontact tonometry. The evaluated outcomes were the presence of fibrovascular tissue and intraocular pressure. This study was done by a surgeon and assisted by a nurse. There are 71 eyes in this study; 10 eyes are lost during follow-up. The 61 eyes were divided into 28 triamcinolone and 33 control group. The recurrence of pterygium was found in 2 (39. 3%) of the triamcinolone group and in (10.7%) of the control group (p=0.16). Eight eyes showed increased ocular pressure, and one patient developed granuloma. Subconjunctival triamcinolone injection after pterygium surgery did not significantly reduce pterygium recurrence.